Ascidian fauna (Tunicata, Ascidiacea) of subantarctic and temperate regions of Chile - Turon, Xavier; Cañete, Juan I.; Sellanes, Javier; Rocha, Rosana M.; López-Legentil, Susanna (Zootaxa, 2016)
We studied the ascidian fauna from two zones located in subantarctic (Punta Arenas, latitude 53º) and temperate Chile (Coquimbo, latitude 29º). The different oceanographic features of the two zones, with influence of the Humboldt Current in the north and the Cape Horn Current System and freshwater inputs in the south, led to markedly different ascidian faunas. A total of 22 species were recorded, with no shared species across the two areas (11 species each). The new species Polyzoa iosune is described, Lissoclinum perforatum is found for the first time in the Pacific Ocean, and Synoicum georgianum and Polyzoa minor are new to the Chilean fauna. The populations of Ciona in the Coquimbo area (formerly attributed to Ciona intestinalis) correspond to the species Ciona robusta. A total of 35 Cytochrome oxidase (COI) sequences of the standard barcode region have been obtained for 17 of the 22 species reported.